Synchronic morphological parsing and suffixal productivity in the Hittite adjective: Considerations on some illustrative examples - Pozza, Marianna (Lingua Posnaniensis, 2026)
The purpose of this article is to analyse some Hittite adjectives, to discuss the different options concerning their morphological parsing – and, if available, their etymology – and to clarify the issues behind the productivity of some specific suffixes.